2x+23=29

Simple and best practice solution for 2x+23=29 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+23=29 equation:


Simplifying
2x + 23 = 29

Reorder the terms:
23 + 2x = 29

Solving
23 + 2x = 29

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-23' to each side of the equation.
23 + -23 + 2x = 29 + -23

Combine like terms: 23 + -23 = 0
0 + 2x = 29 + -23
2x = 29 + -23

Combine like terms: 29 + -23 = 6
2x = 6

Divide each side by '2'.
x = 3

Simplifying
x = 3

See similar equations:

| 4=2x-17 | | (-2m+5)-(3m+1)=34 | | 2n=2n+8 | | 5m=16+-8n | | G(x)=x^2-4x-2 | | .40(b+4)=6 | | 4n=(-8) | | 5t+9=89 | | A=3v^2-33v+54 | | -9(-343)= | | 90=2y-6 | | -6(4x-8)+12=-4x+80 | | F(x)=X^2+3-10 | | -4(7r+5)=204 | | (5k+5)-(-3k+11)= | | 26=8+m | | 2[t+1]=10 | | 2[y+2]=10 | | 5m+8n=16forn | | 4t^3+32= | | f(y)=2x-6 | | 82=8x+2(x+6) | | 20-12x=500 | | 5x=-3x^2+2 | | -3m+2= | | 8x^2+5x+11=0 | | f(x)=-2x^2-20x-54 | | 5x+6-10x=-39 | | x+3/4=9/2 | | 2-x=40 | | .5x+x=490.5 | | 2-x=48 |

Equations solver categories